Introducing LAB60: A 1/60 degree NEMO 3.6 numerical simulation of the Labrador Sea - Pennelly, Clark; Myers, Paul G. (2020)
A high-resolution coupled ocean–sea ice model is set up within the Labrador Sea. With a horizontal resolution of 1/60◦ , this simulation is capable of resolving the multitude of eddies that transport heat and freshwater into the interior of the Labrador Sea. These fluxes strongly govern the overall stratification, deep convection, restratification, and production of Labrador Sea Water. Our regional configuration spans the full North Atlantic and Arctic; however, high resolution is only applied in smaller nested domains within the North Atlantic and Labrador Sea. Using nesting reduces computational costs and allows for a long simulation from 2002 to the near present. Three passive tracers are also included: Greenland runoff, Labrador Sea Water produced during convection, and Irminger Water that enters the Labrador Sea along Greenland. We describe the configuration setup and compare it against similarly forced lower-resolution simulations to better describe how horizontal resolution impacts the representation of the Labrador Sea in the model.